Isolation of Human Metapneumovirus from clinical specimen in human organoid-derived bronchial cell cultures is superior to isolation in monolayer cell line cultures - Ribó-Molina, Pau; van Nieuwkoop, Stefan; Funk, Mathis; Verstrepen, Babs E.; van Kampen, Jeroen J.A.; Fouchier, Ron A.M.; van den Hoogen, Bernadette G. (Journal of clinical virology, 2025)
Human Metapneumovirus (HMPV) is a causative agent of respiratory tract infections (RTI) in children and adults. HMPV is a member of the Pneumoviridae family for which circulation of two serotypes, A and B, has been reported. HMPV isolation in standard monolayer cell lines is not always successful. Recently, it was shown that upon inoculation of human organoid-derived bronchial (ODB) cultures, HMPV primarily targeted the ciliated cells, similar as observed in experimentally infected animals. These observations lead to the hypothesis that isolation of virus from clinical specimen in this ODB model could be more successful than in standard monolayer cultures. This study compared the efficiency of isolation of HMPV from 36 clinical samples in human ODB cultures with that in monolayers of Vero-118 cells. A total of 27 isolates (8 HMPV A and 19 HMPV B) were obtained in the ODB cultures, after one passage, whereas 21 isolates (9 HMPV A and 12 HMPV B) were obtained after one or two passages in Vero-118 cells. Overall, the isolation efficiency of serotype A HMPV was comparable in both models, while isolation of serotype B viruses was profoundly more efficient in the ODB cultures than in Vero-118 cells, suggesting that primary cultures expressing ciliated cells should be considered as a superior isolation method for HMPV from clinical specimens. ●Isolation of HMPV from clinical specimen is challenging and time consuming.●Bronchial cell cultures are useful to isolate HMPV from clinical specimens.●HMPV A Isolation success is comparable in Vero cells and bronchial cell cultures.●HMPV B isolation success in primary bronchial cell cultures is better than in Vero cells.●Genomic single nucleotide variants cannot clearly explain the isolation differences.